Differentiation of Content, Process, and Product in Islamic Religious Education Learning at SD Baitul Amien 1 Jember - Abdullah Hasyim Zain; Mashudi; Saihan (Program Studi PGMI, 2026)
This study aims to analyze the implementation of differentiated instruction encompassing content, process, and product differentiation in Islamic Religious Education (IRE) learning at SD Baitul Amien 1 Jember. The study employed a qualitative approach with a case study design. Data were collected through classroom observations, semi-structured interviews with IRE teachers, students, and school administrators, as well as document analysis. The data were analyzed using thematic analysis involving data reduction, data display, and conclusion drawing, with trustworthiness ensured through source and technique triangulation. The findings reveal that content differentiation was implemented relatively systematically by adjusting the depth of learning materials based on students’ learning readiness. Process differentiation was reflected in the use of varied instructional strategies, flexible grouping, and diverse learning activities, although its implementation was constrained by time limitations and class size. Product differentiation was implemented through providing task options; however, it remained less optimal due to the dominance of written assessments. The study concludes that differentiated instruction has significant potential to enhance student engagement and understanding in Islamic Religious Education at the elementary level. Strengthening assessment flexibility and institutional support is essential to optimize the implementation of differentiated instruction in IRE learning.